Landscape in Technological Image The Complex Aesthetics Perspective (Itinera, 2024)
In the Anthropocene, what contribution to landscape design and creation can the technological image, whose action, or agency, is global in scope?Beyond being a functional backdrop for human action and an object of images provided by devices designed for control in virtual mappings and telematic geolocations, can the landscape also be the subject of technological images that are able to promote a new paradigm of reciprocity between man and cosmos?In an attempt to answer such questions, this contribution is aimed at reconsidering in epistemological terms certain notions of the aesthetics of the technological image and, in particular, of the audiovisual image: immersivity, synesthesia and Stimmung.In the perspective of the development of a complex aesthetics, it is hypothesized that the aesthetic experience of the artistic audiovisual image of the landscape can potentially promote a sensitive knowledge of the environment, capable of contributing to the development of an ecological sensitivity.
Keywords: complex aesthetics, audiovisual experience, sensitive knowledge, cosmocentrism